(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Tariff policies serve as an essential mechanism for emerging markets to harmonize domestic industrial development, trade competitiveness, and global economic integration. This comparative study evaluates India‘s tariff strategies in relation to those of other BRICK countries—Brazil, Russia, China, and South Korea. India‘s strategy is marked by a combination of protectionist measures and gradual liberalization, imposing high tariffs on critical sectors such as automobiles and agriculture to protect local industries. In contrast, China and South Korea have embraced more liberal tariff frameworks to promote export-driven growth and facilitate integration into global value chains. Similarly, Brazil and Russia exhibit a tendency towards protectionism but emphasize regional trade agreements and targeted sectoral support. The analysis reveals significant differences in tariff approaches, regional trade commitments, and integration into global supply chains. It concludes with suggestions for India to lower tariffs on intermediate goods, utilize free trade agreements effectively, and strike a balance between protectionism and liberalization to improve its global trade competitiveness. This study highlights the significance of customized tariff policies in fostering economic growth and global integration for emerging markets, providing valuable insights for policymakers in India and other BRICK nations.